MONTESSORI PEDAGOGY OF PRESCHOOL AGE THE ROLE OF CHILDREN'S DEVELOPMENT (Academicia Globe: Inderscience Research, 2022)
The article discusses the role of Montessori pedagogy in the education of preschool children, its peculiarities, pedagogical conditions and important factors.